ANALISIS PREFERENSI MERK LAPTOP MAHASISWA UNIVERSITAS DIPONEGORO MENGGUNAKAN MODEL LOGIT TERSARANG - Ain Hafidita; A Rusgiyono; Dwi Ispriyanti (Jurnal Gaussian, 2014)
Today’s rapidly evolving information technology affects mostly the change of people’s choice in electronic devices (gadget) usage, especially laptops. Addressing this phenomenon, laptop manufacturers are competing to create innovative products to reach various elements of the consumer. Nested logit, which sorts the alternatives based on common properties into smaller groups (nests) and has a level so as to form a tree structure, is a method that can be used to model consumer preferences. Alternatives may have either unique or common characteristics that describe properties or components so called attributes. In this study, laptop brands are treated as alternatives and classified by the operating system. This research concluded that the most favorite brand is Asus (25.35 %), followed by Toshiba (22.81%), Lenovo (14.27%), HP (13.90%), Acer (12.40%) and the least is Macbook (11.27%). Attributes that significantly affect the brand preferences are laptop classification and warranty, while color is considered insignificant.